Efektivitas Penerapan Sistem Keuangan Desa (Siskeudes) Dalam Meningkatkan Akuntabilitas Laporan Keuangan Desa : (Studi Kasus Desa Dinas Kesiman Petilan, Kecamatan Denpasar Timur) - Indriantini, Ni Wayan Bela; Putu Nuniek Hutnaleontina; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2025)
The purpose of this study is to evaluate how well Kesiman Petilan Village, East Denpasar District, has been able to improve the accountability of village financial reporting by implementing the village financial system (siskeudes). Data collection methods include documentation, interviews, and observation, all of which are done using qualitative descriptive technique. Four participants participated in this study as informants. Kinds of reports, timeliness and correctness of reporting, applicability of requirements, procedures, elucidation of reporting stages, and feedback. Based on both vertical and horizontal accountability indicators, it is possible to draw the conclusion that the village government's reporting and accountability are both good and accountable in terms of the accountability of the village financial reports. Although manual administration requires more time and has the possibility for fraud, this Siskeudes program is more effective and efficient in that regard.